Nanomedicines for brain diseases - Tosi, Giovanni (Henry Stewart Talks, 2018)
The Blood-Brain Barrier in healthy and diseased state, Planning a nano-4-neuro, Strategies for Blood-Brain Barrier crossing with nanotechnology, Technological issues, What we learn and what to do in NPs for CNS, Exploitation of endogenous/exogenous pathways, Proofs of concept and pharmacological evidences, The case of Alzheimer’s Disease: analysis of nanomedicine applications